Introduction to process control - Romagnoli, Jose A. (Jose Alberto) (Chemical industries., 2012)
"Preface When the first edition of this book was published in 2006, there were a number of factors that motivated us to undertake this challenge. These, by and large, still apply as we introduce the second edition. Changing industrial needs and advances in computer technology had, and continue to have, a profound impact on the education, research, and practice of process control. From the industrial perspective, improved productivity, efficiency, and product quality goals generated a demand for more effective operational strategies to be incorporated in the production line, while developments in digital computers and communications revolutionized the practice of process control and allowed more advanced tools to be implemented. As a consequence, we witnessed a vast broadening of the domain of what is technologically and economically achievable in the application of computers to control industrial processes. This domain now includes process information and data gathering, control, and online optimization, and even production scheduling and planning functions. We now view modern process control as an efficient integration of real-time information management with the traditional concept of control. As such, the process control education needs to conform to the current practice and follow the tendencies in the field. With the second edition, our goal is twofold. First, as in the previous edition, we aim to provide a bridge between the traditional view (role) of process control and the current and expanded view (role). This is accomplished by blending traditional topics with a broader perspective of more integrated process operation, control, and information systems"--